2017
DOI: 10.5385/nm.2017.24.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Caffeine in Korean Preterm Infants with Apnea of Prematurity

Abstract: Purpose: Caffeine shows wide interindividual pharmacokinetic (PK) variation, and therapeutic drug monitoring (TDM) may be needed. The PK profile of caffeine in Korean preterm neonates was investigated, and factors influencing the clearance of caffeine were analyzed. Methods: Fifty-nine preterm neonates receiving caffeine for apnea of prematurity were enrolled in the study (gestational age, 29.5±2.2 weeks and birth weight [BW], 1,318±358 g). Caffeine (20 mg/kg) was intravenously administered to each neonate as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
2
1
Order By: Relevance
“…The pharmacokinetics parameters of caffeine in preterm neonates of this study were compared with those reported previously (Table 5). Interestingly, we found that the CL value estimated from our study was larger than that of most researches from Australia and Europe, whereas less than the Korean value reported by Lim et al Nevertheless, the value of V in the Korean study was lower than all other researches, in which our value was the largest 6–9,27 . From the available data, it cannot be confirmed whether this phenomenon is due to regional differences or the deviation is resulted from limited subjects.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…The pharmacokinetics parameters of caffeine in preterm neonates of this study were compared with those reported previously (Table 5). Interestingly, we found that the CL value estimated from our study was larger than that of most researches from Australia and Europe, whereas less than the Korean value reported by Lim et al Nevertheless, the value of V in the Korean study was lower than all other researches, in which our value was the largest 6–9,27 . From the available data, it cannot be confirmed whether this phenomenon is due to regional differences or the deviation is resulted from limited subjects.…”
Section: Discussioncontrasting
confidence: 96%
“…A two‐compartment model showed no improvement to OFVs and one‐compartment model with first‐order elimination was successfully fitted to the data, which agreed with the results reported previously 6–9 . Exponential functions were selected to model the inter‐individual variability for CL and residual error.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Caffeine has interethnic pharmacokinetic differences. CYP1A2 is the main caffeine metabolism enzyme encoded by the CYP1A2 gene which has gene polymorphism leading to interindividual variability [ 9 , 10 ]. Although a recent study concluded that there was no significant association between CYP1A2 gene variation and caffeine pharmacokinetic parameters [ 10 ], the genetic polymorphisms in caffeine targeting the adenosine receptor induced different clinical responses to caffeine therapy [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%